Makna TakfÃ®r Pemimpin bagi Kaum Salafi - Muliono, Slamet (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
This article provides one of salafi?s views about takfîr against state leaders. Islamic da?wah movements, have so far, asserted that takfîr is allowed in order to find and to point out the best leader who inclines to implement Islamic doctrines within nation-state context. Takfîr, in the view of Islamic da?wah movements, has emerged as a result of leader?s reluctance or failure to implement the Islamic sharîa within nation-state?s life. However, in the view of salafi groups, takfîr through coup d?état would likely obliterate the state order. The salafi groups view that this sort of takfîr, which aims to replace leadership through coup d?état, was Khawârij?s ideology. Nevertheless, the salafi groups emphasize that there would be no guaranty for a better leadership after coup d?état. It has, even so, often led to the emergence of worse leadership which creates social disorder.